IMPLEMENTASI AUGMENTED REALITY (AR) DI PERGURUAN TINGGI MENGGUNAKAN UJI-T BERPASANGAN - Sihotang, Siti Fatimah (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
Today, higher education faces growing challenges in integrating technology to enhance unique and innovative student learning experiences. One technology that has been in the spotlight in recent years and is very widely used today is Augmented Reality (AR). Considering that currently, there are still many students who have difficulty understanding learning concepts well, have difficulty applying the material studied in everyday life, it is hoped that the use of Augmented Reality (AR) in higher education can be a solution. Augmented Reality (AR) can change the way students view learning as well as its extensive use which can also be felt by all elements of the academic community at universities as tertiary institutions. Thus, this research aims to find out how much influence the use of Augmented Reality (AR) has in universities, namely lecturers, students and universities. The method used in this research is paired t-test. From the research results, it is known that the application of Augmented Reality (AR) has a significant effect in higher education with an effectiveness value of 70% which is included in the interpretation category of effectiveness as quite effective